Incorporating the five pillars of pancasila for enhancing anti-fragility in sustainable umkm development - Diah Ayu Septi Fauji; Heri Pratikto; Agung Winarno; Puji Handayati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Micro, Small, and Medium Enterprises (UMKM) play a vital role in the global economy, including in Indonesia, where their functions and definitions may vary across different countries. This research explores the integration of Pancasila values in fostering the sustainable development of UMKM in Indonesia, emphasizing ethical business practices and inclusivity. Conducted in East Java, the study involved 220 UMKM actors and focused on analyzing the influence of Pancasila-based performance factors on UMKM resilience. Using factor analysis, the study examines the effects of Pancasila values on UMKM resilience, demonstrating the high validity and reliability of the instruments used. The findings highlight that the adoption of Pancasila values significantly enhances the resilience of UMKM, particularly in terms of their ability to adapt and thrive in challenging conditions. The results also underscore the importance of integrating ethical, social, and cultural values into business practices to ensure long-term economic sustainability. These insights can inform practical strategies for managing UMKM and shaping policies that foster their growth and resilience.